Customers acceptance and usage, purchase behaviour and post purchase behaviour of self- ordering kiosk technology in quick-service restaurants: moderating roles of perceived safety risk and age generation / Noradzhar Baba - Baba, Noradzhar (2021)
The self-service technologies (SST) were one of the technologies used in quick-service restaurant to supplement the usual face-to-face interaction while ordering food. Even though the self-service technology had been in the market for quite some time, the adoption of the technology had yet to receive attention from the foodservice industry player in Malaysia. On one hand, the millennial or younger generation was seen as the perfect target candidate that would accept the self-service technology in the quick service restaurant, on the other hand, the older generation still prefer the conventional ordering methods as they did not trust the usage of electronic payment. Furthermore, the current situation was exacerbated due to the sudden emergence of Covid-19 pandemic. Due to its high infectivity potential, there was a serious concern when the customers wanted to utilize the touchscreen-based self-service technology. Therefore, it was crucial to explore how Covid-19 pandemic affects customers’ purchase behaviour via the self-ordering kiosk. This study empirically discovers customer acceptance and usage of a self-ordering kiosk, purchase behaviour, and post-purchase behaviour in a quick-service restaurant. The present study adopted the use of Unified Theory of Adoption and Use of Technology (UTAUT2) as the study framework. This study adopted a quantitative research methodology using a survey questionnaire as the main data collection method with cross-sectional time horizon. 430 questionnaires were able to be obtained from the data collection process. Data collected were analyzed to yield descriptive statistics and PLS-SEM was used to test the hypotheses of the study and evaluate a model. Additionally, multivariate analysis was used to identify technology use between age groups. The result indicated that customers’ trust was the most significant predictor in the acceptance and use of a self -ordering kiosk. Multivariate analysis revealed that younger generation was inclined toward utilitarian factors (performance expectancy, effort expectancy, facilitating condition) while the hedonic motivation was found to be stronger in the older generation. The result from the present study verified that the UTAUT2 model could be integrated into the research of self-ordering kiosk technology acceptance and use especially in a Malaysian context. The inclusion of safety risk also enhances the use of UTAUT2 in a pandemic situation. Given the positive outlook from the respondents, quick-service restaurant industry should continuously improve its self-ordering kiosk efficiency. Given differences in age generation, the different interfaces should be designed to serve different age groups.